Aplicação dos recursos do PRONAF na primeira década do Século XXI: uma análise comparativa entre a Bahia, o Nordeste e o Brasil - SANTOS, Leandro Tavares dos (2013)
The aim of this thesis was to understand the distribution pattern of the applications of the National Program for Strengthening Family Agriculture (Pronaf) in Bahia, occurred in the first decade of this century, after the start of a government whose party has seemingly showed more concerned with social causes. It is proposed here that the argument Pronaf would be managed, in recent years, with a logic that seek to mitigate the distortions in the application of its resources. It was used as a methodology in exploratory work, with which we used a literature and analysis of data, using, for this purpose the data provided by the Department of Family Agriculture (SAF), an agency under the Ministry of Development (MDA) and the figures released by the Census of Agriculture 2006 - IBGE, as one of the parameters to assess the distribution of these resources. Thus, this study was divided into four chapters, the first of which were treated some elements which introduce the theme, plan a broader discussion on the what is called the "agrarian question". The next chapter discusses up on the family farm in the national context. Already in chapter three, are dealt two of the most recent policies aimed at family producer. And, at last, is performed the data analysis Pronaf in Bahia, where he undertakes a comparison of the data found in the Northeast and in Brazil. Among the findings it was found throughout the 2000s a trend towards regional concentration of resources Pronaf more precisely south of the country, at the expense of other regional scales such as the Northeast and Bahia which are quantitative rather superior family farms.